Hilma af Klint: from the spirit to matter - Cheles, Anna Carolina (2019)
The multiple questions related to the esoteric work of Hilma af Klint are in-creasingly relevant nowadays. The move-ment around the artist is not by chance. From the dubious title of abstractionist avant-garde pioneer to an expressive link between the spiritual and the mate-rial world, the artist is emphasized by the coinciding paths in the artistic universe of Wassily Kandinsky and Piet Mondrian, through concepts and philosophy based on Helena Blavatsky and Rudolf Stein-er Theosophy, which would be in wide circulation aiming a spiritual search vis-à-vis the modernist progress at the end of the 19th century. Hilma af Klint, how-ever, presents a trajectory of her own in which her spirituality overlays her work with a deeply religious and mediumistic character, not found in her already men-tioned pairs. Behaving less as a modern artist and more as a priestess, Klint and her work inquire what Walter Benja-min would conceptualize as the auratic character of works of art, since her work stresses the secular and the divine, the traditional and the modern in a unique way and quite different from what would be done by the abstractionists.